2008
DOI: 10.7863/jum.2008.27.8.1129
|View full text |Cite
|
Sign up to set email alerts
|

Bifid Median Nerve in Patients With Carpal Tunnel Syndrome

Abstract: A bifid median nerve occurs relatively frequently in patients with CTS. It may facilitate compression of the median nerve in the carpal tunnel because of its relatively higher cross-sectional area compared with a nonbifid median nerve. The size criterion for CTS in patients with a bifid median nerve is slightly higher than in those with a nonbifid median nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
128
5
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(143 citation statements)
references
References 21 publications
7
128
5
3
Order By: Relevance
“…In contrast with this study, Bayrak et al, 11 reported a higher prevalence of BMN in patients with CTS (19% in CTS and 9% in control group) in their study having the largest sample among studies investigating the association between BMN and CTS. They suggested that BMN might facilitate compression of the nerve in the carpal tunnel due to its relatively higher CSA compared with a non-BMN.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In contrast with this study, Bayrak et al, 11 reported a higher prevalence of BMN in patients with CTS (19% in CTS and 9% in control group) in their study having the largest sample among studies investigating the association between BMN and CTS. They suggested that BMN might facilitate compression of the nerve in the carpal tunnel due to its relatively higher CSA compared with a non-BMN.…”
Section: Discussioncontrasting
confidence: 46%
“…1 In previous studies, BMN was reported to be associated with CTS due to its relatively higher cross sectional area (CSA) compared to a non-BMN which may lead compression in carpal tunnel. 1,[11][12][13] However, in a more recent study Granata et al, 14 reported similar frequencies of BMN in patients with CTS and the healthy control group. Hence, we aimed to determine the BMN frequency in patients with CTS and healthy control group, and to investigate the aforementioned association between CTS and BMN in our population.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The various differences of the incidence maybe because of various diagnostic tools or ethnic groups. In addition, several reports have suggested that the bifid median nerve can be a causative factor for carpal tunnel syndrome 8 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the hypotheses is that the bifid median nerve may facilitate compression of the nerve in the carpal tunnel because of larger summated cross-sectional area compared with the cross-sectional area of a non-bifid median nerve 8 . In contrast, some authors recently reported that the bifid median nerve is not an independent risk factor for development of carpal tunnel syndrome 7,9 .…”
Section: Discussionmentioning
confidence: 99%